SECONDARY METABOLITES OF HIGHER PLANTS AS GROWTH REGULATORS FOR ONIONS - A. D. Borovskaia; N. A. Mashcenсo; A. V. Gumaniuk (Овощи России, 2018)
Possibility of pre-sowing seed treatment with growth regulators of steroid and iridoid nature has been studied while growing onions. In the experiment, an "ecostim" preparation has been used for the pre-sowing treatment of onion seeds, the active ingredient of which is the glycoside of the steroid nature of tomatosides isolated from the seeds of Solanum lycopersicum L., as well as the sum of iridoid glycosides (linarosides) from Linaria vulgaris Mill. To identify the technological parameters of the use of plant growth bio-regulators preliminary testing has been conducted in the Laboratory of Natural Bio-Regulators of the Institute of Genetics, Physiology and Plant Protection, A comparison of the effectiveness of the compounds obtained on the germination of onion seeds has shown that the greatest stimulation has been achieved by using low concentrations (0.0001% - 0.001%) of tomatoside solutions (eostimis preparation) and higher concentrations (0.005% - 0.01%0 of linarosides. Production tests have been carried out in the field in the Pridnestrovian Research Institute of Agriculture. Variety specificity of the impact of natural bio-regulators has been determined by the example of 3 varieties of onions, different in terms of maturation, resistance, etc. (Pinguin, Diamant and Chalcedon). It has been proved that the effect of the tested growth regulators has a pronounced varietal specificity and mainly is determined by the early maturity of the variety. It has been found that the compounds studied were most effective when growing onions under unfavorable conditions, and the amount of iridoid glycosides from the linaria had a greater stimulating effect compared with the tomatoside. Seed treatment with bio-regulators has provided the simultaneous emergence of seedlings, the leveling in growth and development of plants, as well as increased the yield of onions by 27.6% - 41.3%.